The dead ringer/retained transcriptional regulatory gene is required for positioning of the longitudinal glia in the Drosophila embryonic CNS. - Shandala, T.; Takizawa, K.; Saint, R. (Development, 2003)
The Drosophila dead ringer (dri, also known as retained, retn) gene encodes a nuclear protein with a conserved DNA-binding domain termed the ARID (AT-rich interaction domain). We show here that dri is expressed in a subset of longitudinal glia in the Drosophila embryonic central nervous system and that dri forms part of the transcriptional regulatory cascade required for normal development of these cells. Analysis of mutant embryos revealed a role for dri in formation of the normal embryonic CNS. Longitudinal glia arise normally in dri mutant embryos, but they fail to migrate to their final destinations. Disruption of the spatial organization of the dri-expressing longitudinal glia accounts for the mild defects in axon fasciculation observed in the mutant embryos. Consistent with the late phenotypes observed, expression of the glial cells missing (gcm) and reversed polarity (repo) genes was found to be normal in dri mutant embryos. However, from stage 15 of embryogenesis, expression of locomotion defects (loco) and prospero (pros) was found to be missing in a subset of LG. This suggests that loco and pros are targets of DRI transcriptional activation in some LG. We conclude that dri is an important regulator of the late development of longitudinal glia.